Q: What is the solution to y equals 2x - 3 x plus y equals 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 3 = 72x = 4x = 2

2x+3 = 3x+5 2x-3x = 5-3 -x = 2 x = -2

According to my calculations, yes. 2x+8=3x+11 -8 2x=3x+3 -2x 0=x+3 -3 -3=x

x = 3 and y = 2

5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2

Related questions

2x + 3 = 72x = 4x = 2

x=-2

2x+3 = 3x+5 2x-3x = 5-3 -x = 2 x = -2

According to my calculations, yes. 2x+8=3x+11 -8 2x=3x+3 -2x 0=x+3 -3 -3=x

5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2

x = 3 and y = 2

x = 0 & y = -3

x = 3, y = 3

x - 3y = -3: multiply by -2 giving -2x + 6y = 6, but -2x + 6y = 12 so we have a problem! Misprint?

x = 1 and y = 2

2x - 3 = 2x - 52x = 2x - 22x - 2x = -20 =/= -2Zero is not equal to -2 so the answer is no solution.

(2x - 10) + 7 = 52x - 3 = 52x = 8x = 4